The Lasting Effects of Early Childhood Education on Promoting the Skills and Social Mobility of Disadvantaged African Americans - Jorge Luis García; James J. Heckman; Victor Ronda (Institute of Labor Economics (IZA), 2021)
This paper demonstrates multiple beneficial impacts of a program promoting inter-generational mobility for disadvantaged African-American children and their children. The program improves outcomes of the first-generation treatment group across the life cycle, which translates into better family environments for the second generation leading to positive intergenerational gains. There are long-lasting beneficial program effects on cognition through age 54, contradicting claims of fadeout that have dominated popular discussions of early childhood programs. Children of the first-generation treatment group have higher levels of education and employment, lower levels of criminal activity, and better health than children of the first-generation control group.
Keywords: J13; I28; C93; H43; 330; early childhood education; intergenerational mobility; racial inequality; social mobility